Business models of foreign subsidiary units of international companies – theoretical considerations - Benabdallah, Mounia; Ćwik, Krzysztof; Kachour, Maher; Krzos, Grzegorz; Leszczynska, Dorota; Olek, Krystian; Piwoni-Krzeszowska, Estera (Management Sciences, 2016)
On the basis of the study of literature the article discusses the types of roles played by foreign units of international companies and synthetically presents the problem of business models focusing on the perspective of the internationalization of business operations. That provided the basis for the identification of the main areas requiring scientific research into the business models of foreign units of international companies. The gaps are presented in the form of the following research questions: what are the elements of the business models of foreign units of international companies; do the same elements constitute the business models of international companies and their foreign units; what types of business models of foreign entities exist; what internal factors determine the choice of business models of foreign units of international companies; is there a correlation between the country of origin of an international company and types of business models of its foreign units? Defining these questions helped designate the trajectory of research which is necessary to enrich the scientific research into the problems of business models of foreign units of international companies
Nauki o Zarządzaniu = Management Sciences, 2016, Nr 4 (29), s. 9-27
Keywords: business model; internationalisation; international company; foreign unit of international company; model biznesu; internacjonalizacja; międzynarodowe przedsiębiorstwo